Consideration of comorbidity in risk stratification prior to prostate biopsy. Issue 13 (25th April 2013) - Liss, Michael A.; Billimek, John; Osann, Kathryn; Cho, Jane; Moskowitz, Ross; Kaplan, Adam; Szabo, Richard J.; Kaplan, Sherrie H.; Greenfield, Sheldon; Dash, Atreya
Abstract : BACKGROUND: Previously, the patient‐reported Total Illness Burden Index for Prostate Cancer (TIBI‐CaP) questionnaire and/or the physician‐reported Charlson Comorbidity Index (CCI) have provided assessments of competing comorbidity during treatment decisions for patients with prostate cancer. In the current study, the authors used these assessments to determine comorbidity and prognosis before prostate biopsy and the subsequent diagnosis of prostate cancer to identify those patients least likely to benefit from treatment. METHODS: A prospective observational cohort study was performed of 104 participants aged 64.0 years ± 6.5 years from 3 institutions representing different health care delivery systems. Patients were identified before undergoing transrectal ultrasound‐guided prostate biopsy and followed for a median of 28 months. Associations between the comorbidity scores and nonelective hospital admissions were investigated using logistic regression and Cox proportional hazards models. RESULTS: Among the 104 patients who underwent prostate biopsy, 2 died during the follow‐up period. The overall hospital admission rate was 20% (21 of 104 patients). Higher scores on both the TIBI‐CaP (≥ 9) and CCI (≥ 3) were found to be significantly associated with an increased odds for hospital admission (odds ratio, 11.3 [95% confidence interval (95% CI), 2.4‐53.6] and OR, 5.7 [95% CI, 1.4‐22.4]) and hazards ratios (HRs) for time to hospital admission (HR, 3.8 [95% CI, 1.3‐11.2] and HR, 3.2 [95% CI, 1.1‐9.1]), respectively. CONCLUSIONS: TIBI‐CaP and CCI scores were found to successfully predict which patients were at high risk for nonelective hospital admission. These patients are likely to have poorer health and a potentially shortened lifespan. Therefore, comorbidity analysis using these tools may help to identify those patients who are least likely to benefit from prostate cancer therapy and should avoid prostate biopsy. Cancer 2013;119:2413‐2418 . © 2013 American Cancer Society . Abstract : Organizations are recommending the use of life tables or comorbidity assessment in patients before prostate cancer screening or prostate biopsy to reduce overtreatment; however, they do not provide specific means for comorbidity analysis. In the current study, the authors present the Charlson Comorbidity Index and the patient‐reported Total Illness Burden Index for Prostate Cancer (TIBI‐CaP) as tools to predict acute hospital admission as a surrogate for poor overall health and those patients who should avoid prostate biopsy.